Towards an Indian Christian Theology of Religious Pluralism - Vineeth, V F (Journal of Dharma, 1989)
The following is the statement of the thirteenth annual meeting of the Indian Theological Association (ITA) held at St Paul's Seminary, Thiruchirappalli, from December 28-31, 1989 on the theme, 'Towards an Indian Christian Theology of Religious Pluralism.' Of the four research papers presented in the seminar by Gispert Sauch, V.F. Vineeth, Dominic Veliath and Raimundo Panikkar, the paper of V. F. Vineeth is reproduced in this issue with the kind permission of the ITA. Editor